The Effect of Continuous Multistage Countercurrent Extraction (CMCE) Propolis Extract Administration on Leydig, and Sertoli Cells Counts, and Sperm Quality Induced With Monosodium Glutamate (MSG) (An experimental study on male Wistar rat induced by monosodium glutamate) - Rahmawati, Rahmawati; Nasihun, Taufiqurrachman; Isradji, Israhnanto (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
INTRODUCTION:Â ROS is the most common cause of male infertility. Monosodium glutamate (MSG) is a compound which produces ROS and decreases FSH and LH levels. Continuous Multistage Countercurrent Extraction (CMCE) propolis extract as an antioxidant is evidently capable of reducing ROS concentration.OBJECTIVE: this research aims at evaluating the effect of CMCE propolis extract administration on Leydig cells and Sertoli cells counts and sperm quality of MSG-induced male wistar rats.METHODS: employing the Post Test Only Control Group Design, 18 rats were divided into 3 groups: control group, treated only with MSG (MS-G), and treatment groups, respectively treated with CMCE propolis extract at doses 8.3mg/day (CM8-G) and 10.8mg/day (CM10-G). CMCE propolis extract was given orally for 21 days. At the end of treatment, sperm and testis were taken to evaluate the Leydig cells and Sertoli cells counts and sperm quality. The sperm obtained from epididymis was analyzed using the WHO standards, while Leydig cells and Sertoli cells were counted from preparation using the HE stain method.RESULTS: the Post Hoc analysis result shows that the Leydig and Sertoli cells counts and sperm quality of CM8-G and CM10-G are significantly higher than those of MS-G, p<0.05. The Leydig cells and Sertoli cells counts and sperm quality of CM10-G are significantly higher than those of CM8-G, p><0.05. CONCLUSION: CMCE propolis extract administration evidently increases the Leydig cells and Sertoli cells counts and sperm quality from the perspective of the count, motility and morphology of spermatozoa of MSG-induced male wistar rats.><0.05CONCLUSION: CMCE propolis extract administration evidently increases the Leydig cells and Sertoli cells counts and sperm quality from the perspective of the count, motility and morphology of spermatozoa of MSG-induced male wistar rats.Â